Structure Enhancement Relationship of Chemical Penetration Enhancers in Drug Transport across the Stratum Corneum - Doungdaw Chantasart; S. Kevin Li (MDPI AG, 2012)
The stratum corneum is a major barrier of drug penetration across the skin in transdermal delivery. For effective transdermal drug delivery, skin penetration enhancers are used to overcome this barrier. In the past decades, a number of research studies were conducted to understand the mechanisms of skin penetration enhancers and to develop a structure enhancement relationship. Such understanding allows effective prediction of the effects of skin penetration enhancers, assists topical and transdermal formulation development, and avoids extensive enhancer screening in the transdermal delivery industry. In the past two decades, several hypotheses on chemical enhancer-induced penetration enhancement for transport across the skin lipoidal pathway have been examined based on a systematic approach. Particularly, a hypothesis that skin penetration enhancement is directly related to the concentration of the enhancers in the stratum corneum lipid domain was examined. A direct relationship between skin penetration enhancer potency (based on enhancer aqueous concentration in the diffusion cell chamber) and enhancer n-octanol-water partition coefficient was also established. The nature of the microenvironment of the enhancer site of action in the stratum corneum lipid domain was found to be mimicked by n-octanol. The present paper reviews the work related to these hypotheses and the relationships between skin penetration enhancement and enhancer concentration in the drug delivery media and stratum corneum lipids.